Respuesta :

Answer:

The answer is 7/12.

Step-by-step explanation:

[tex]( \frac{2}{3} - \frac{1}{4} ) + ( \frac{1}{2} \times \frac{1}{3} )[/tex]

Solve the terms in the bracket first

That's find the LCM of the ones which are subtracting

LCM of 3 and 4 is 12

That's

[tex] \frac{2}{3} - \frac{1}{4} = \frac{8 - 3}{12} = \frac{5}{12} [/tex]

Next multiply the other terms in the other bracket

That's

[tex] \frac{1}{2} \times \frac{1}{3} = \frac{1}{6} [/tex]

Add both results

That's

[tex] \frac{5}{12} + \frac{1}{6} [/tex]

Find the LCM

The LCM is 12

We get the final answer as

[tex] \frac{5}{12} + \frac{1}{6} = \frac{5 + 2}{12} = \frac{7}{12} [/tex]

Hope this helps you